Passive exercise is an effective alternative to HRT for restoring OVX induced mitochondrial dysfunction in skeletal muscle - Hu, Yi; Fang, Biqing; Tian, Xu; Wang, Haiwei; Tian, Xiangyang; Yu, Fangfang; Li, Tao; Yang, Zhijie; Shi, Rengfei (Frontiers in Endocrinology, 2024)
Background: Postmenopausal women are more prone to develop muscle weakness, which is strongly associated with impairment of mitochondrial function in skeletal muscle. This study aimed to examine the impact of a passive exercise modality, whole-body vibration training (WBVT), on muscle mitochondrial function in ovariectomized (OVX) mice, in comparison with 17β-estradiol (E2) replacement. Methods: Female C57BL/6J mice were assigned to four groups: sham operation control group (Sham), ovariectomized group (OVX), OVX with E2 supplement group (OVX+E), and OVX with WBVT group (OVX+W). The estrous cycle, body weight, body composition, and muscle strength of the mice were monitored after the operation. Serum E2 level was assessed by enzyme-linked immunosorbent assay (ELISA). The ATP levels were determined using a luciferase-catalyzed bioluminescence assay. The activity of mitochondrial respiration chain complexes was evaluated using high-resolution respirometry (O2K). Expression levels of oxidative phosphorylation (OXPHOS), peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC-1α), and mitochondrial transcription factor A (TFAM) were detected using western blotting. Results: We observed decreased muscle strength and impaired mitochondrial function in the skeletal muscle of OVX mice. The vibration training alleviated these impairments as much as the E2 supplement. In addition, the vibration training was superior to the ovariectomy and the estradiol replacement regarding the protein expression of PGC-1α and TFAM. Conclusions: WBVT improves the OVX-induced decline in muscle strength and impairment of mitochondrial function in the skeletal muscle. This passive exercise strategy may be useful as an alternative to E2 replacement for preventing menopausal muscular weakness. Further studies are needed to understand the effects of WBVT on various physiological systems, and precautions should be taken when implementing it in patient treatment.